“It’s been years and it still hurts”: Paediatric Critical Care staff experiences of being involved in serious investigations at work: a qualitative study - Morrison, R; Yeter, E; Syed-Sabir, H; Butcher, I; Duncan, H; Webb, S; Shaw, R (Springer International Publishing, 2024)
Background: Evidence conducted globally has shown that patient care improves when staff are well. Investigations, although necessary to understand errors and unanticipated events, can be distressing. Feelings of shame and guilt are associated with making mistakes and can lead to moral injury. Objective: To explore staff experiences of investigations to develop a staff care package. Design: Exploratory qualitative. Setting(s): Paediatric Critical Care (PCC) in a UK quaternary hospital. Participants: 14 doctors and nurses. Methods: PCC staff who had experienced an investigation were interviewed individually. Transcripts were analysed using thematic analysis. Results: Fourteen interviews were conducted. Investigations involved Serious incidents, Disciplinary, and Professionalism cases. Four main themes related to: (1) Emotional impact; (2) Negotiating process; (3) Communication challenges; (4) Needing support. Conclusions: This research has identified aspects of the investigation process which can be upsetting for staff, cause unnecessary distress or moral injury. Findings informed a model for a Feelings First Care Pathway for Serious Investigations.